Long‐term Outcome of Isobar TTL System for the Treatment of Lumbar Degenerative Disc Diseases - Junhu Li; Qiujiang Li; Zhipeng Deng; Linnan Wang; Lei Wang; Yueming Song (Orthopaedic Surgery, 2024)
Objective The Isobar TTL dynamic fixation system has demonstrated favorable outcomes in the short‐term treatment of lumbar degenerative disc diseases (LDDs). However, there is a paucity of extensive research on the long‐term effects of this system on LDDs. This study aimed to evaluate the long‐term clinical and radiological outcomes of patients with LDDs who underwent treatment utilizing the Isobar TTL dynamic fixation system. Methods The study analyzed the outcomes of 40 patients with LDDs who underwent posterior lumbar decompression and received single‐segment Isobar TTL dynamic internal fixation at our hospital between June 2010 and December 2016. The evaluation of clinical therapeutic effect involved assessing postoperative pain levels using the visual analogue scale (VAS) and Oswestry disability index (ODI), both before surgery, 3 months after, and the final follow‐up. To determine the preservation of functional motion in dynamically stable segments, we measured the range of motion (ROM) and disc height of stabilized and adjacent segments preoperatively and during the final follow‐up. Additionally, we investigated the occurrence of adjacent segment degeneration (ASD). Results Forty patients were evaluated, with an average age of 44.65 years and an average follow‐up period of 79.37 months. Fourteen patients belonged to the spondylolisthesis group, while the remaining 26 were categorized under the stenosis or herniated disc group. The preoperative ROM of the stabilized segment exhibited a significant reduction from 8.15° ± 2.77° to 5.00° ± 1.82° at the final follow‐up (p < 0.001). In contrast, there was a slight elevation in the ROM of the adjacent segment during the final follow‐up, increasing from 7.68° ± 2.25° before surgery to 9.36° ± 1.98° (p < 0.001). The intervertebral space height (IH) in the stabilized segment exhibited a significant increase from 10.56 ± 1.99 mm before surgery to 11.39 ± 1.90 mm at the one‐week postoperative follow‐up (p < 0.001). Conversely, there was a notable decrease in the IH of the adjacent segment from 11.09 ± 1.82 mm preoperatively to 10.86 ± 1.79 mm at the one‐week follow‐up after surgery (p < 0.001). The incidence of ASD was 15% (6/40) after an average follow‐up period of 79.37 months, with a rate of 15.38% (4/26) in the stenosis or herniated disc group and 14.29% (2/14) in the spondylolisthesis group; however, no statistically significant difference was observed in the occurrence of ASD among these groups (p > 0.05). Conclusion The Isobar TTL dynamic fixation system is an effective treatment for LDDs, improving pain relief, quality of life (QoL) and maintaining stabilized segmental motion. It has demonstrated excellent long‐term clinical and radiographic results.